(untitled) (Research, Society and Development, 2020)
Direct solar radiation on the cover of poultry houses is one of the main factors that hinder the homeothermic process, causing thermal stress to birds and immediately reflecting on their productive and physiological performance. Brazil being a tropical country tends to have regions that are characterized by having hot or very hot summers, providing birds with higher levels of heat stress. The objective of this review is to approach the influence of coverings with different types of materials in their composition on the thermal performance of poultry houses for broilers, in different regions of Brazil. An exploratory review of the bibliographic field was used as the method. Poultry grows every year and in the search for improvements in the facilities applying to a good accommodation of birds, research has been looking at the materials that make up the roof of poultry buildings aiming to associate the efficiency of reflectance and the accessible cost, in the development animals in an environment of thermal comfort. In short, the definition of the roofing material in the facilities in order to achieve better conditions for agricultural production will depend on the region, correlating the types of construction materials with the climatological knowledge of the local referent. We highlight the imposition of more in-depth studies on these construction methods, as well as exploring the possibilities that already exist, with the purpose of seeking improvements to obtain an effective and affordable material.